Identification and Mapping of Flood Vulnerability in the Meninting Watershed, West Lombok - Arben Virgota; Baiq Farista; Suripto; Lalu Adi Gunawan; Ernawati (Postgraduate, University of Mataram, 2024)
Flooding is the inundation of a flat area as a result of overflowing water from the surrounding area or an overflowing river. The largest river that crosses West Lombok Regency is the Meninting River. The Meninting watershed area as a catchment area has an area of 12,307.75 hectares. This research aims to identify and map flood-vulnerability areas in the Meninting Watershed. Data collection was carried out through a geographic information system (GIS) using overlay and scoring methods. The variables used to assess the level of flood vulnerability were land slope, soil type, rainfall, land cover, and geological aspects. The level of flood vulnerability is divided into three classes, namely not vulnerable, moderately vulnerable, and very vulnerable. The results show that of the 41 villages/sub-districts in the Meninting watershed, 34 villages/urban- villages with a coverage area of 8.21% were very vulnerable to flooding. The four villages that have the largest flood-vulnerable areas were the villages of North Ampenan (120.16 hectares), Midang (87.43 hectares), Dasan Griya (79.68 hectares), and Sesela (77.32 hectares). Around 56.24% of all villages/urban villages in the Meninting watershed were quite vulnerable to flooding and 35.55% of the area was not vulnerable.